Mindfulness and life satisfaction: The moderating effect of self-control and the moderated moderating effect of resilience. (February 2022) - Liang, Sancai; Dong, Meimei; Zhao, Hongbin; Song, Yuliang; Yang, Anqi
Abstract: Studies have revealed that mindfulness is related to life satisfaction. However, little was known about under which conditions mindfulness is associated with life satisfaction. The present study aimed to explore the moderating roles of self-control and resilience in the association between mindfulness and life satisfaction. Four hundred and ninety-four Chinese undergraduates filled the questionnaires that measure mindfulness, self-control, resilience, and life satisfaction. The results indicated that self-control moderated the association between mindfulness and life satisfaction so that this association was only significant for individuals with high self-control but not for individuals with low self-control. The moderating role of self-control was further moderated by resilience, so that at high and average levels of resilience, mindfulness and self-control interacted to influence life satisfaction; whereas at low levels of resilience, this interaction was insignificant. Limitations and implications are discussed. Highlights: Self-control moderates the association between mindfulness and life satisfaction. The moderating effect of self-control is further moderated by resilience. The moderating effect of self-control only exists for high resilient individuals.